Animal personality and state–behaviour feedbacks: a review and guide for empiricists. (January 2015) - Sih, Andrew; Mathot, Kimberley J.; Moirón, María; Montiglio, Pierre-Olivier; Wolf, Max; Dingemanse, Niels J.
Highlights Animal personalities can be explained by state–behaviour positive feedback loops. Relevant state variables include both intrinsic and extrinsic factors. We discuss experimental and statistical methods for studying state–behaviour feedbacks.